EFFICIENT TWO-SERVER PASSWORD-ONLY AUTHENTICATED KEY EXCHANGE - Miss. Alfiya Bagwan; Miss. Manjusha Nawale; Miss. Sana Mulani; Miss. Priyanka Jagtap; Guide- Prof. Kumbhar P.B. (International Journal of Innovations in Engineering Research and Technology, 2021)
Password-authenticated key exchange (PAKE) is placed in between client and a main server, which is used to share a password and authentication of password and in parallel establish a cryptographic key by exchanging messages. While doing these settings the entire password are stored in mainframe server. If the server is hacked or even malfunction happens due to internal system password stored will be open to hacker. This paper is written for consideration a two main servers operate in hand shake mode and one of them is hacked or malfunctioning. The advantage of this system even if one system is hacked, the hacker will not be able to see anyone’s password or any other information. The proposed system proposes two servers, using password-authenticated key exchange(PAKE). In this case two servers will operate in handshake mode, and contribute to a generation of one key for authentication. Proposed system presents a symmetric solution for two server by using PAK, where client will get access to two different servers using cryptographic keys. The protocol develops runs in parallel operation to save time, and it is found that it is more secure and efficient than existing system.